An international survey of maximum surgical blood ordering schedule creation and compliance. (29th May 2019) - Yazer, Mark H.; Kutner, Jose; McCabe, Julie; O'Donghaile, Diarmaid; Pendergrast, Jacob; Treml, Angela; Wendel, Silvano; Yan, Matthew; Ye, Zhan; Yokoyama, Ana Paula; Cohn, Claudia S.
Abstract : Background and Objectives: Maximal surgical blood order schedules (MSBOS) are prepared to assist surgeons and anaesthesiologists with pretransfusion test orders. The literature on the prevalence and usefulness of MSBOS in international settings is lacking. We developed a survey to understand the prevalence of MSBOS in hospitals and to analyse compliance with MSBOS recommendations. Method and Materials: A survey tool was developed by the Biomedical Excellence for Safer Transfusions (BEST) collaborative. The survey link was distributed to BEST members who were encouraged to forward the link to colleagues. Survey respondents were asked to contribute data regarding their hospital's MSBOS and MSBOS compliance. Results: There were 174 completed surveys. Greater than half of respondents did not have an MSBOS. The total number of beds was significantly different ( P  = 0·04) in hospitals with (N = 81) or without (N = 93) an MSBOS. Less than a quarter of respondents felt that their MSBOS was being followed despite widespread access to the MSBOS. Over 60% of type and screen orders were MSBOS compliant; however, just 42% of cross‐match orders were compliant. There was a significant difference between the number of red‐blood‐cell units returned to the blood bank when comparing MSBOS compliant and MSBOS non‐compliant cross‐match orders (227 versus 788 units, respectively, P  = 0·0026). Conclusions: An  MSBOS could be a useful tool to help with pretransfusion test orders; however,  the majority of respondents lacked a MSBOS. In hospitals with a MSBOS, it was reported to be under‐utilized, which might contribute to the low compliance rates seen for cross‐match orders.